Morfofunctional Characteristics of a Sample From First B Chilean Professional Football Players According to Playing Position - Velásquez-González, Hugo (2020)
Objective: to analyze the morphofunctional profile of Chilean professional soccer players according to their playing position. Method: the study design was non-experimental, with a descriptive-correlational scope. Twenty-nine professional soccer players belonging to the Valdivia Sports Club of Chile were evaluated. Fat percentage was established by measuring four skin folds and applying the Durnin and Womersley equation. For the physical variables, the maximum squat repetition test was applied, and the Brzycki method was used to project the maximum force in one repetition. In explosive force, the Bosco Test was performed; this test evaluates the squat jump (SJ). The level 1 recovery Yoyo Test was used for the aerobic resistance, with heart rate (HR) measurement at the end and in recovery (1 minute). Results: Only significant differences in height are observed between goalkeepers and midfielders (F = 4.491; p = 0.012); this implies that age, weight, and Σ4 folds do not affect in the playing position. Conclusions: it is observed that, in each game position, the players present a different morphofunctional configuration, which allows inferring that the work must be differentiated.